PENGARUH MERCHANDISE, ATMOSFER GERAI DAN PELAYANAN RITEL TERHADAP PERILAKU PEMBELIAN IMPULSIF PADA HARDY’S MALL GIANYAR - Trisnu, Cokorda Gde Cahaya Putra; Santika, I Wayan (E-Jurnal Manajemen, 2015)
The purpose of this study was to determine the effect of merchandise, atmosphere and service retail outlets to purchase behavior impulsuf on Hardy's Mall Gianyar This study used a quatitative analysis using surveys and questionnaires to 120 Hardys’s Mall Gianyar consument. The results of this study stated that merchandising positive and significant effect on impulsive buying behavior in Hardy's Mall Gianyar. Furthermore, the atmosphere stores positive and significant effect on impulsive buying behavior on Hardy's Mall Gianyar and retail services have significant positive effect on impulsive buying on Hardys's Mall Gianyar.
Keywords: Merchandise; Atmosfer Gerai; Pelayanan Ritel; Pembelian Impulsif